Pengaruh pengelolaan sarana dan prasarana terhadap peningkatan mutu pendidikan di sekolah - Farkhanuddin, Muhammad (Jurnal Madako Education, 2025)
Every human being has the right to develop their potential, and education is the primary means to achieve this. The government plays a crucial role in regulating the education system to ensure effective learning and the production of competent and competitive human resources. This study aims to analyze the management of facilities and infrastructure in improving the quality of education. The method used is a qualitative research method with a library research approach, which is sourced from books, scientific journals, articles, and theses relevant to the research topic. Educational facilities and infrastructure, often referred to as infrastructure, are essential and interrelated components that support the smooth running of the learning process in schools. The study results indicate that good management of facilities and infrastructure, including planning, procurement, utilization, and maintenance, contributes significantly to improving the quality of education. With optimal management, teaching and learning activities become more effective, students feel comfortable, and teachers can carry out their duties optimally. Therefore, the management of facilities and infrastructure is not merely a technical support but a strategic factor in realizing quality education.